A novel approach for ultrasensitive amperometric determination of NADH via graphene-based electrode obtained by electrochemical intercalation of tetraalkylammonium ions - Dokur, Ebrar; Uruc, Selen; Gorduk, Ozge; Sahin, Yucel (SPRINGER HEIDELBERG, 2023)
The reduced beta-nicotinamide adenine dinucleotide (NADH) is an important coenzyme in many biological systems. In this work, a new electrochemical sensor platform prepared using tetraoctylammonium ions (TOA(+)) as an intercalant for the intercalation with graphite electrode is reported to determine NADH efficiently. While NADH detection was performed using amperometry at 0.55 V, the characterization of the developed sensor was examined using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), electrochemical impedance spectroscopy (EIS), Fourier transform infrared spectroscopy (FT-IR), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, and cyclic voltammetry (CV) techniques. The manufacture of the modified electrode is easy, and the repeatability of the signal process is good enough for NADH determination. The developed NADH sensor showed excellence in the low detection and quantitation limit, high sensitivity, good stability, and specificity. The proposed TOA(+)/PGE-based electrochemical sensor displayed good analytical performance and LOD and LOQ values were calculated as 0.077 mu M and 0.257 mu M, respectively. In addition, the effect of TOA(+)/PGE on the analysis of species that may show interference effects found in real samples was examined. It proved that the sensor could successfully detect the NADH level in the human blood sample.
Keywords: Reduced beta-nicotinamide adenine dinucleotide; Intercalation; Pencil graphite electrode; Cyclic voltammetry; Non-enzymatic sensor; NICOTINAMIDE ADENINE-DINUCLEOTIDE; CARBON NANOTUBE SENSOR; PASTE ELECTRODE; GRAPHITE-ELECTRODES; VOLTAMMETRIC DETECTION; EXFOLIATION; PERFORMANCE; OXIDATION; DOPAMINE; AMMONIUM; Chemistry; Electrochemistry; Physics